3D imaging based on fringe effect of an electrical capacitance tomography sensor. (October 2015) - Sun, Jiangtao; Yang, Wuqiang; Tian, Wenbin
Highlights: 3D ECT imaging based on fringe effect is further investigated in details . Comparison between imaging results with different measurement scenarios. The use of different reconstruction algorithms and data interpolation methods. Experimental verification of the proposed method. Abstract: Conventionally, electrical capacitance tomography (ECT) provides 2D images. While 3D imaging by ECT with multi-plane electrodes has been attempted, 3D imaging with a single-plane ECT sensor is a new topic. While it has been confirmed that a 3D imaging method based on the fringe effect of a single-plane ECT sensor is feasible for imaging of a metallic object in a high permittivity background, this paper presents further investigation into imaging a metal object or a dielectric object in a low permittivity background. Different image reconstruction algorithms and data interpolation methods are used. This proposed method has been verified both by simulation and experiment.